MEMBANGUN KARAKTER SISWA MELALUI BIMBINGAN KONSELING - Evita Dwi Mirnandy; Triono Ali Mustofa (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
Education is a stage in developing, growing and maturing a personality which is related to increasing quality human resources. Education plays a very important role in improving human life so that they live a much better quality life and are active in socializing in society. Character Education is an educational system that has the aim of cultivating individual character in students. Lately there has been a lot of news regarding bad phenomena out there that can affect the lives of students in a very deviant way. The role of guidance and counseling teachers, who are often called school counselors, has an important role in shaping the character of students both inside and outside school. Therefore, students can build character which can be done by executing learning programs to improve students' character cannot be successful if they do not contribute to related parties, especially in the field of education. Therefore, counseling guidance participates in this contribution. In this case the author tries to explain the task of counselors to shape student character, learning about student character education in counseling guidance services and the task of counselors to shape student character. This research uses qualitative methods to describe the results of this research discussion.